SOLUSI HAMPIRAN PERSAMAAN LOGISTIK NON-AUTONOMOUS - Mohamad Riyadi; Daswa Daswa (Jurnal Edukasi dan Sains Matematika (JES-MAT), 2019)
The aim of this study is to derive the approximation solution of the non-autonomous logistic equation with a non-constant carrying capacity. The solution is found via predictor-corrector method (Adams-Bashforth-Moulton method, Milne method and Hamming method). The approximation solution that obtained, then, is compared to the exact solution. The results show that, for small step size, the approximation solution approximate the exact solution is in good agreement.